Banoks Ihaw-Ihaw Davao barbecue at its best - Villanueva, Manuel Paul H.; Concepcion, Sylvia B.; Soledad, Miguel D. (Davao City School of Management, University of the Philippines Mindanao, 2006)
Davao's food industry, particularly the chicken barbecue and lechon manok sector, is faced with a lot of challenges amidst the growing competition and the discriminating preferences of consumers. Despite being an active player in the previous 10 years, Banoks Ihaw-ihaw continues to struggle against the pressure of sustaining its profitability and maximizing its growth potential. As the population grows, consumer demand within the food industry is expected to increase correspondingly. Coupled with the favorable location of its restaurants, Banoks intends to capitalize on the quality and value of its product offerings in meeting customers' requirement for value, good taste and convenience. Opportunities for expansion in untapped areas within and beyond Mindanao also abound and this further presents challenging prospects for the business. This study is prepared to carefully assess the firm's internal conditions in relation to its external environment to map out an auspicious future for Banoks. Survival is not the main purpose. Rather, this strategic plan intends to equip Banoks with the appropriate strategic tools to effectively compete in an industry where rivalry among the players is increasingly becoming intense, gain a huge chunk of the market, and eventually become the industry leader. The firm already possesses a couple of advantages over its rivals but the low entry barriers in the food industry heighten the existing level of competition. This paper recommends offering Banoks to interested industrial and financial partners who can contribute professional expertise in managing the enterprise and infuse additional equity. This strategy is expected to acquire additional ammunition to repackage the ten-year company image into a brand new retail identity.
Thesis, Graduate (Master in Management)--University of the Philippines Mindanao, April 2006.
Keywords: Strategic plan